Discovery of a giant deep-sea valley in the Indian Ocean, off eastern Africa: the Tanzania channel - (:unkn) unknown (My University, 2008)
During the Fanindien 2006 cruise of R/V ‘Beautemps-Beaupré’, high resolution multibeam bathymetry, sub-bottom profiling and sediment coring was carried out along the East African margin, offshore Tanzania and Mozambique (Indian Ocean). The newly acquired data reveal the presence of a giant deep-sea valley (the Tanzania channel) that is more than 10 km wide at 4000 m water depth, along the continental rise. The valley remains 70 m deep and 7 km wide at 800 km from the Tanzania coast. Morphological comparison with worldwide submarine channels show that the Tanzania channel is one of the largest known submarine valleys. This discovery brings new light on development of submarine valleys that drain sediments originated from the East African Rift System (EARS) highlands (i.e. the Tanzania channel and its neighbor Zambezi channel located 1000 km southward). Both of the systems have a morphology markedly different to the classical sinuous, V-shaped channels located at similar latitudes (e.g. the Zaire or Amazon channels). Their submarine drainage system consists of a downslope converging tributary canyons joining a central trunk channel in the continental rise. The presence of such giant deep-sea drainage systems is probably linked to a strong structural control on the sediment pathway, associated to a massive sediment transfer towards the Indian Ocean in relation with the tectonic activity of the East African Rift System (i.e. the uplift periods trough mid-Miocene and Plio-Pleistocene times) and its interplay with the East African equatorial climate changes.
Keywords: African Research